IMPLEMENTASI GAME EDUKATIF BERBASIS QUIZIZZ UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK - Muhammad Hasani Zuhri; Suadi (As-Sulthan Journal of Education, 2026)
This study aims to describe the implementation of Quizizz-based educational games in Akidah Akhlak learning, analyze students' learning interest after the application of Quizizz media, and identify the supporting and inhibiting factors. This research uses a qualitative approach with a descriptive type. The research location is at MA YTI Nguling, Pasuruan, involving the Akidah Akhlak teacher and 11th-grade students (14 students). Data collection techniques include participant observation, in-depth interviews, and documentation study. Data analysis was performed through data reduction, data display, and conclusion drawing/verification. The validity of the data was ensured through prolonged engagement, source and method triangulation, and member checking. The findings reveal that: (1) The implementation of Quizizz was carried out through three stages: planning, execution, and evaluation; (2) Students' learning interest significantly increased across all four indicators: feelings of enjoyment, attention and concentration, activeness and engagement, and interest in continuous learning; (3) Supporting factors include device availability, student enthusiasm, teacher support, and Quizizz features; while inhibiting factors include device limitations, signal interference, and initial student distraction. This research contributes to the modification of digital media implementation theory and formulates the principle of "Meaningful Digital Wasilah" in an Islamic perspective.